2016
DOI: 10.1007/s10162-016-0567-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Histone Deacetylases Attenuate Noise-Induced Hearing Loss

Abstract: Loss of auditory sensory hair cells is the major pathological feature of noise-induced hearing loss (NIHL). Currently, no established clinical therapies for prevention or amelioration of NIHL are available. The absence of treatments is due to our lack of a comprehensive understanding of the molecular mechanisms underlying noise-induced damage. Our previous study indicates that epigenetic modification of histones alters hair cell survival. In this study, we investigated the effect of noise exposure on histone H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 34 publications
(23 reference statements)
4
33
0
Order By: Relevance
“…iHDACs are also known to reduced noise-, gentamicin-, and cisplatin-induced ototoxicity [ 15 , 16 , 17 , 26 ]; however, the mechanism by which this occurs remains unclear. In the present study, iHDAC treatment increased both TRIC and LSR expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…iHDACs are also known to reduced noise-, gentamicin-, and cisplatin-induced ototoxicity [ 15 , 16 , 17 , 26 ]; however, the mechanism by which this occurs remains unclear. In the present study, iHDAC treatment increased both TRIC and LSR expression.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs have a crucial role in both, transcription regulation and protein modification [ 30 ]. Previous studies have identified iHDACs as a promising strategy for therapeutic intervention in cancer, neurological disorders, immune disorders31, and hearing loss [ 15 , 16 , 17 , 26 ]. The deacetylation of histone core proteins may trigger cell death; thus, iHDACs could function to attenuate the apoptotic-signaling pathways involved in noise-induced hearing loss [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in recent years, several less toxic HDAC inhibitors have been tested in clinical trials or are already approved by the FDA for the treatment of cancer. Among these, SAHA (vorinostat) attenuated hearing loss in mice caused by treatment with the combination of kanamycin (KM) and furosemide or by noise (Layman et al, 2015 ; Wen et al, 2015 ; Chen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%